Changes in the Ixodes ricinus microbiome associated with artificial tick feeding - Militzer, Nina; Pinecki Socias, Sophia; Nijhof, Ard M. (Frontiers in Microbiology, 2023)
Artificial tick feeding systems (ATFS) can be used to study tick biology and tick-pathogen interactions. Due to the long feeding duration of hard ticks, antibiotics are commonly added to the in vitro blood meal to prevent the blood from decaying. This may affect the ticks’ microbiome, including mutualistic bacteria that play an important role in tick biology. This effect was examined by the consecutive feeding of Ixodes ricinus larvae, nymphs, and adults in vitro with and without the supplementation of gentamicin and in parallel on calves. DNA extracted from unfed females was analyzed by 16S rRNA sequencing. The abundance of Candidatus Midichloria mitochondrii, Rickettsia helvetica and Spiroplasma spp. was measured by qPCR in unfed larvae, nymphs, and adults. Larvae and nymphs fed on calves performed significantly better compared to both in vitro groups. Adults fed on blood supplemented with gentamicin and B vitamins had a higher detachment proportion and weight compared to the group fed with B vitamins but without gentamicin. The detachment proportion and weights of females did not differ significantly between ticks fed on calves and in vitro with gentamicin, but the fecundity was significantly higher in ticks fed on calves. 16S rRNA sequencing showed a higher microbiome species richness in ticks fed on calves compared to ticks fed in vitro. A shift in microbiome composition, with Ca. Midichloria mitochondrii as dominant species in females fed as juveniles on calves and R. helvetica as the most abundant species in females previously fed in vitro was observed. Females fed in vitro without gentamicin showed significant lower loads of Ca. M. mitochondrii compared to females fed in vitro with gentamicin and ticks fed on calves. Spiroplasma spp. were exclusively detected in female ticks fed on cattle by qPCR, but 16S rRNA sequencing results also showed a low abundance in in vitro females exposed to gentamicin. In conclusion, the employed feeding method and gentamicin supplementation affected the ticks’ microbiome composition and fecundity. Since these changes may have an impact on tick biology and vector competence, they should be taken into account in studies employing ATFS.